Research on policies of power batteries recycle in China from the perspective of life cycle - Wang, Di (Journal of Environmental Engineering and Landscape Management, 2021)
As fueled by the rapid advancement of novel energies-based vehicles in our nation since 2015, Chinese production and ownership of novel energies-based vehicles in China have been leaping forward. According to 4—8 years’ service life of power batteries, China ushered into the large-scale scrapping phase of power batteries in 2019, so the power batteries recycle system should be urgently constructed. Given the life cycle perspective, the characteristics of each stage of the power battery life cycle are analyzed in the present study. As revealed from the results, the upstream end of the power batteries recycle system in China is not yet perfect, the production capacity at the midstream end tends to be excess, and the downstream end is in the exploratory phase. Moreover, the present study analyzes the policies throughout the life cycle of power batteries, and it is reported that the recycling policies at the midstream processing end are relatively concentrated, the upstream and downstream policies are comparatively deficient, the top-level legal construction is lacked, the recycling network is not perfect, and the incentive and guidance policies for echelon exploitation enterprises require modification, and relevant policy suggestions are proposed.